Music and Mediated Religious Identity "Jesus Freak" - Radwan, Jon (2006)
Contemporary Christian Music (CCM) is a genre that uses popular styles to express religious ideas. "Jesus Freak" (McKeehan & Heimermann, 1995), an enormously successful CCM song, is approached from the perspective of constitutive rhetorical theory. Both lyrics and music are critiqued to determine how the song invites its teen audience to develop shared definitions of Self and Other. Lyrically the song creates a Freak subject position for young Christians that meets mainstream secular judgment with pride and defiant indifference. Musically, a fusion of grunge and rap styles is combined with harmonic and rhythmic composition techniques, such as direct allusions to hit songs by Nirvana and the appropriation of historically non-Christian perfect discords, to demonstrate how being a Christian can be rebellious and cool. Close textual-musical analyses can move us beyond traditional theories of influence derived from linguistic persuasion and into conceptions of mediated and presentational "proof" that more fully account for how contemporary media do ideological work.